Elucidating Therapeutic and Biological Potential of Berberis baluchistanica Ahrendt Bark, Leaf, and Root Extracts - Gul, Zareen; Akbar, Ali; Leghari, Saadullah Khan (Frontiers in Microbiology, 2022)
Berberis baluchistanica Ahrendt is a medicinal plant known to have potential for the treatment of various diseases. In present study the ethanolic extracts of bark, leaves and roots of Berberis baluchistanica plant were evaluated for in-vitro antimicrobial, anti-leishmanial, anticancer and anti-inflammatory activities. The antibacterial and antifungal activities were determined by agar mix and agar well diffusion method. All extracts showed potential activity against the target bacterial (Bacillus subtilis, Bacillus licheniformis, Escherichia coli,Klebsiella pneumoniae, Pseudomonas aeruginosa, Rhodococcus erythropolis, Salmonella typhi and Staphylococcus aureus) and fungal strains(Aspergillus flavus, Aspergillus niger and Mucor mucedo). Staphylococcus aureus proved to be the most sensitive strain for each extract with maximum zone of inhibition for bark(23±0.12mm),for leaves(22±0.36mm)and for roots extract(20.21±0.06mm). The Minimum Inhibitory Concentration(MIC) values of Berberis baluchistanica bark, leaves and roots for different target bacterial strains ranged from 1.56-25 mg/ml and Minimum Bactericidal concentrations(MBC) were in the range of3.12-25mg/ml respectively. The root extract possessed potent antifungal activity against A. flavus with 83% of growth inhibition and A. niger with 80%and M. mucedo with 73%inhibition. Bark extract was found active against M. mucedo with 86%of inhibition followed by 70% against A. flavus and 60%against A.niger. Leaves extract showed significant response by 83% inhibition against M. mucedo followed by A. flavus and A. niger with 73% and 72% inhibition respectively. In anti-leishmanial bioassay the inhibitory concentration(IC50) was observed for each extract against Leishmania major, the bark showed good activity(IC50=4.95±0.36 mg/mL),followed by roots(IC50=7.07±0.18mg/mL),and leaves(IC50=8.25±0.29mg/mL). Evaluation of anticancer activity was done by using MTT cell assay against HeLa cell line. Comparing the values of each extract to the standard revealed that the ethanolic bark extract showed highest anticancer activity with IC50=(12±0.15µg/mL)followed by roots 14±0.15µg/mL)and leaves(17±0.21µg/mL)respectively. The anti-inflammatory assay was undertaken by the inhibition of albumin denaturation activity, proteinase inhibitory activity and heat induced hemolysis activity. The IC50 value for protein denaturation of the bark was IC50=0.64±0.25mg/mL followed by roots 0.67±0.21mg/mL and leaves 0.73±0.13mg/mL. The proteinase inhibitory activity of bark extract was with IC50=0.55±0.12mg/mL followed by leaves 0.62±0.23mg/mL and roots 0.69±0.15mg/mL respectively. For heat induced hemolysis assay, bark showed lowest IC50 value(0.48±0.15mg/mL)as compared to leaves(0.52±0.35mg/mL) and roots(0.58±0.05mg/mL) of the plant.